Simultaneous multi-colony tracking of a pelagic seabird reveals cross-colony utilization of a shared foraging area - Dean, B; Kirk, H; Guilford, T; al., E (Inter-Research, 2015)
The role that population-level competition plays in regulating foraging distributions of colonial breeders has remained elusive because many studies of animal movements in the natural environment focus on relatively small datasets from a single population of animals. Here, we present a large (528 foraging trips, 169 individuals), multi-year, multi-colony GPS tracking dataset mostly collected simultaneously at 4 breeding colonies across the core breeding range of a colonially breeding pelagic seabird, the Manx shearwater Puffinus puffinus. Foraging areas were identified by filtering GPS locations (using speed, time of day, and turning angle), validated on a subset of 25 birds carrying co-deployed depth loggers to maximise inclusion of foraging and feeding behaviour. Foraging areas showed high annual variation, but consistent patterns emerged. Birds from each colony consistently foraged locally, showing little overlap between colonies, but birds from all 4 colonies sometimes travelled large distances to forage within a single relatively restricted area. This combined pattern may be driven by density-dependent competition relatively locally, with high overlap and resource sharing at a distance, facilitated by a dual foraging strategy of mixing short and long trips. The key shared area was located near to a tidal front system, the Irish Sea Front, and the stratified waters of the Western Irish Sea to its north and west, which are characterised by high productivity. Visits to this area declined with increasing colony distance, suggesting that foraging advantages are balanced by the energetic costs of travel. Nevertheless, this area is probably of key importance to birds breeding at colonies across the species’ core breeding range, highlighting the potential connectedness, and therefore vulnerability, of a pelagic species via a single foraging location, despite apparent segregation more locally around the breeding colonies.